Salud emocional y apoyo familiar en joven con discapacidad intelectual grave - Ochoa Vera, Malena Mickaela (Machala: Universidad Técnica de Machala, 2024)
This paper analyzes the influence of emotional health and family support in a 20 year old young man with severe intellectual disability, diagnosed 11 years ago. Residing in El Guabo canton, El Oro province, the young man belongs to a single-parent family and faces difficulties in managing his emotions and behaviors, which impacts both his family and educational environment. This research highlights the relevance of the family as a fundamental nucleus for affective, ethical and social development, pointing out that challenging behaviors are linked to parenting styles and mechanisms used to promote the emotional health of the individual. Severe intellectual disability implies significant limitations in the development of practical, social and conceptual skills, which requires constant support in different aspects of daily life. In addition, a close relationship is observed between this condition and possible affectations in mental health, underlining the importance of appropriate interventions. In this case, the young man shows challenging behaviors, such as disobedience at home and mood swings at school, which highlights the need to understand and strengthen the support he receives. The paper is structured in four chapters. The first deals with the conceptualization of severe intellectual disability and its relationship with emotional health. The second develops the theoretical and epistemological framework. The third details the qualitative and descriptive approach adopted. Finally, the fourth presents the results, conclusions and recommendations, emphasizing strategies to improve the quality of life of the young person and his or her environment.
Este trabajo analiza la influencia de la salud emocional y el apoyo familiar en un joven de 20 años con discapacidad intelectual grave, diagnosticado desde hace 11 años. Residente en el cantón El Guabo, provincia de El Oro, el joven pertenece a una familia monoparental y enfrenta dificultades para gestionar sus emociones y conductas, lo que impacta tanto en su entorno familiar como educativo. Esta investigación destaca la relevancia de la familia como núcleo fundamental para el desarrollo afectivo, ético y social, señalando que las conductas desafiantes están vinculadas a los estilos de crianza y mecanismos utilizados para fomentar la salud emocional del individuo. La discapacidad intelectual grave implica limitaciones significativas en el desarrollo de habilidades prácticas, sociales y conceptuales, lo que exige apoyo constante en diferentes aspectos de la vida cotidiana. Además, se observa una estrecha relación entre esta condición y posibles afectaciones en la salud mental, subrayando la importancia de intervenciones adecuadas. En este caso, el joven muestra comportamientos desafiantes, como desobediencia en el hogar y cambios de humor en el colegio, lo que resalta la necesidad de comprender y fortalecer el apoyo que recibe. El trabajo se estructura en cuatro capítulos. El primero aborda la conceptualización de la discapacidad intelectual grave y su relación con la salud emocional. El segundo desarrolla el marco teórico y epistemológico. El tercero detalla el enfoque cualitativo y descriptivo adoptado. Finalmente, el cuarto presenta los resultados, conclusiones y recomendaciones, enfatizando estrategias para mejorar la calidad de vida del joven y su entorno.
Keywords: DISCAPACIDAD INTELECTUAL; SALUD EMOCIONAL; CONDUCTA DESAFIANTE; APOYO FAMILIAR